A commutant realization of Odake's algebra - Creutzig, Thomas; Linshaw, Andrew R. (Transformation Groups, 2013)
The bcβγ-system W of rank 3 has an action of the affine vertex algebra V0(sl2), and the commutant vertex algebra C = Com(V0(sl2),W) contains copies of V-3/2(sl2) and Odake's algebra O. Odake's algebra is an extension of the N = 2 super-conformal algebra with c = 9, and is generated by eight fields which close nonlinearly under operator product expansions. Our main result is that V-3/2(sl2) and O form a Howe pair (i.e., a pair of mutual commutants) inside C. More generally, any finite-dimensional representation of a Lie algebra g gives rise to a similar Howe pair, and this example corresponds to the adjoint representation of sl2. © 2013 Springer Science+Business Media New York.
CRIS-Team Scopus Importer:2024-06-24